RESPON TANAMAN LOBAK TERHADAP PEMBERIAN KOMBINASI KOTORAN BEBEK DAN KALIUM DI TANAH PODSOLIK MERAH KUNING - Mayumas Sanaya; astina astina; henny sulistyowati (Jurnal Sains Pertanian Equator, 2019)
The porpose of this study was to determine the best dose combination of duck  manure and potassium manure against the growth and yield of radish in red yellow podzolic soil. This experiment, done at  Garden of the Faculty of Agriculture, Tanjungpura University, Pontianak. The duration of  the study is 52 days, starting on 30 April - 21 June 2018. The research design used in this study was Completely Randomized Design (CRD) with  9 levels of  combinations treatment of duck manure and potassium manure namely k1 = 5 tons / ha duck manure + 40 kg / ha KCl, k2 = 5 tons / ha duck manure + 50 kg / ha KCl, k3 = 5 tons / ha duck manure + 60 kg / ha KCl, k4 = 10 tons / ha duck manure + 40 kg / ha KCl, k5 = 10 tons / ha duck manure + 50 kg / ha KCl, k6 = 10 tons / ha duck manure + 60 kg / ha KCl, k7 = 15 tons / ha duck manure + 40 kg / ha KCl, k8 = 15 tons / ha duck manure + 50 kg / ha KCl, k9 = 15 tons / ha duck manure + 60 kg / ha KCl. Each treatment was repeated three times, and the experimental unit consisted of 3 plant samples. Variable observed dry weight of the upper part of the plant, tuber diameter, tuber length, plant fresh weight and fresh weight of tuber / plant. The results showed that the combination of  duck manure and potassium manure on  red yellow podzolic soil for radish growing media gave a response that was not significantly different in all observation variables namely plant dry weight, the diameter of tube, tuber length, plant fresh weight and fresh weight of tuber. The effective dose to support the growth and yield of radish plant is the combination of duck manure dan KCl with a dose 5 ton/ha duck manure and 40 kg/ha KCl   Keywords: duck manure and potassium manure, red yellow podzolic, radish